Factors Affecting the Adoption of Smartwatch for Tracking Health - Chankong, Nuntaphon; Boonyagul, Sani; Thongpance, Nuntachai; Mekkaew, Chairat; Wongkamhang, Anantasak (International Journal of Membrane Science and Technology, 2023)
Smartwatches are widely used now for a variety of functions, from keeping track of time as they would have in the past to getting general wearer data—including activity data, which is a feature that is particularly well-liked. Wearing a smartwatch can offer additional advantages, such as useful health-related data. By examining exercise, sleep, the accuracy of health information, and pricing value as external factors, this study investigates important aspects influencing the adoption of smartwatch technology and tests hypotheses within the conceptual model of a technological acceptance model (TAM). In order to ascertain the correlations between these characteristics, a comprehensive statistical analysis and structural equation modeling (SEM) were performed on a sample of 200 participants who had undergone screening in Thailand. The findings of this research show that factors such as exercise, sleep patterns, the quality of health information, perceived utility, and pricing value all have a substantial impact on people’s intentions to use smartwatches for tracking their health. The goal of the study is to offer a comprehensive knowledge of the variables affecting the uptake of wearable health monitoring equipment. Additionally, this article offers more details about customer preferences for using smartwatches to track health.